Analisis Pengaruh Harga Pokok Produksi Berbasis Metode Variabel Costing Terhadap Penetapan Harga Jual pada UMKM Pisang Keju Sukodono Cabang Sidodadi - Anita Dwi Setiyawati; Jihan Afiyah; Muhammad Arya Irsya Dani; Siti Aisah; Pingkia Angelica Taufani; M. Ryan Najwa Syihab; Dian Fahriani (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This research was conducted at UMKM Pisang Keju Sukodono, which operates in the food industry. The study aims to analyze the calculation of the cost of production as a basis for determining the selling price using the variable costing method. The data used in this research consists of qualitative data obtained from primary and secondary sources. The results show that calculating the cost of production using the variable costing method provides a more structured guideline for determining the selling price of UMKM Pisang Keju Sukodono's products.